2023
DOI: 10.1101/2023.07.14.549063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postsynaptic mitochondria are positioned to support functional diversity of dendritic spines

Abstract: Postsynaptic mitochondria are critical to the development, plasticity, and maintenance of synaptic inputs. However, their relationship to synaptic structure and functional activity is unknown. We examined a correlative dataset from ferret visual cortex with in vivo two-photon calcium imaging of dendritic spines during visual stimulation and electron microscopy (EM) reconstructions of spine ultrastructure, investigating mitochondrial abundance near functionally- and structurally-characterized spines. Surprising… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Information on animals, survival viral injections, cranial window implantation are described in depth in our previous studies (Scholl et al, 2017(Scholl et al, , 2019(Scholl et al, , 2021Thomas et al, 2023). Briefly, layer 2/3 neurons of the primary visual cortex of female ferrets (n = 3, Marshall Farms) were driven to express the Ca 2+ indicator GCaMP6s via a Cre-dependent AAV expression system.…”
Section: Animals Viral Injections and Cranial Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on animals, survival viral injections, cranial window implantation are described in depth in our previous studies (Scholl et al, 2017(Scholl et al, , 2019(Scholl et al, , 2021Thomas et al, 2023). Briefly, layer 2/3 neurons of the primary visual cortex of female ferrets (n = 3, Marshall Farms) were driven to express the Ca 2+ indicator GCaMP6s via a Cre-dependent AAV expression system.…”
Section: Animals Viral Injections and Cranial Windowsmentioning
confidence: 99%
“…Although a great number of spines are co-tuned with the somatic output (Scholl et al, 2021), there is considerable diversity in orientation preference across the population of spines on a neuron (Scholl and Fitzpatrick, 2020). We previously found that dendritic mitochondria tend to be located near spines that are more diverse in their preferences, suggesting enhanced energetic support (Thomas et al, 2023). This inspired us to consider whether differentially-tuned spines require more astrocytic support.…”
Section: Pap Coverage Supports Dendritic Spine Visual Activitymentioning
confidence: 99%